Computed tomographic signs of hyoid apparatus disease in 165 horses - Hartl, Bettina; Strohmayer, Carina; Vali, Yasamin; Lyrakis, Manolis; Kneissl, Sibylle M. (Frontiers in Veterinary Science, 2025)
IntroductionHorses with hyoid bone disease may present with clinical symptoms such as exercise intolerance, resistance to ridden work, anorexia, or headshaking. This study aims to describe the computed tomographic (CT) signs and prevalence of hyoid disease and to evaluate their association with other CT changes of the head.MethodsIn this study, four investigators conducted a retrospective analysis of their findings after reviewing the medical records of 200 horses that had undergone CT scans between 2009 and 2019. A total of 32 parameters were analyzed, and associations were evaluated between those parameters and the effects of age, weight, and use on the development of hyoid bone disease.ResultsThe temporohyoid joint (THJ) exhibited the most common CT signs, with 52% of cases showing marginal exostosis of the temporal bone, 44.4% displaying osteophytes of the proximal stylohyoid, and 40.2% demonstrating reduced tympanohyoid on the examined sides. The most frequently observed CT signs at the styloceratohyoid/epiceratohyoid joint were marginal exostosis of the distal stylohyoid, identified in 29.0% of the examined sides, and osteoproliferative changes of the proximal ceratohyoid, present in 16.5% of the examined sides. CT signs of disease were rarely found at the ceratobasihyoid joint. Pathological CT signs of the ceratobasihyoid joint were associated with those of the styloceratohyoid/epiceratohyoid joint, and disease in this joint was associated with those of the THJ. The findings of the present study revealed an age-related effect on the occurrence of marginal exostosis and osseous cyst-like lesions (OCLLs) of the temporal bone, as well as on OCLLs and osteophytes of the proximal stylohyoid, and on the thickening of the THJ, and a reduction in the tympanohyoid. Age was also found to influence the incidence of the two styloceratohyoid/epiceratohyoid joint CT signs: marginal exostosis of the distal stylohyoid and osteoproliferative changes at the proximal ceratohyoid. The weight and use of the horses did not affect the occurrence of the evaluated changes.ConclusionCT signs of disease of the hyoid apparatus are common and should be considered as part of the differential diagnosis when examining a horse with poor performance, riding complaints, or headshaking.